Oltre l’impasse del moderno. Un esercizio di koinologia - Cera, Agostino (B@belonline, 2024)
Moving from a suggestion by Jean-François Lyotard, the paper deals with a small exercise in ‘koinology’, namely the attempt to (re-)establish a common and shared dimension to face our times; a framework which takes up the modern Leitmotiv without emulating it. The argument consists of two parts. In the first part, the koinological instance is compared with an unprecedented risk that has emerged in the context of COVID-19 pandemic: an event that perfectly symbolizes the post- or hyper-modern condition. Against the backdrop of a “pandemic society” looms the bogeyman of the idioverse: an echo-cosmos that each person builds (and inhabits) for their own use and consumption, within which every common/shared horizon turns out to be impossible. The idioverse makes every possible koinè a chimera, eclipsing it even as a requirement. The second part presents a framework within which the koinological instance can be restarted. This is the Anthropocene, interpreted as an aspiring new métarécit rather than a geological epoch. The paper focuses on the political-ideological implications of the Anthropocene, particularly those related to anthropological universalism, that is, the legitimacy of the prefix “anthropos” to name this unprecedented epochal scenario.